IMPROVING THE QUALITY OF LEARNING AND SCHOOL MANAGEMENT THROUGH CAMPUS TEACHING PROGRAM COLLABORATION AT SMPN 3 INGIN JAYA - Aini, Qurratu; Fairuzzabadi, Fairuzzabadi; Amukti, Chika Adistia (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2025)
This community service activity aims to enhance the quality of learning and school management through the collaboration of the Kampus Mengajar (Teaching Campus) program at SMPN 3 Ingin Jaya. This program was initiated based on the school’s need to optimize teaching and learning processes as well as to improve administrative management. The methods implemented included mentoring teachers in applying active learning strategies, guiding students to improve literacy and numeracy skills, and assisting school management in administrative governance and the use of information technology. The results of the program indicated increased student learning motivation, enhanced teacher competence in utilizing innovative learning media, and improvements in the school’s administrative systems. The collaboration between the university and the school through the Kampus Mengajar program is expected to serve as a sustainable partnership model to support quality improvement in partner schools.